ATTITUDES OF UNIVERSITY STUDENTS TOWARD HOAXES - Saputra, Dadang Herli (Lingual Journal of Language and Culture, 2020)
The present study aimed to analyse the students’ attitudes toward hoaxes and the other fake news. The research questions were formulated as the followings: a) What are attitudes of students toward hoax? b) What are the factors (determinants) which might affect their behaviour toward hoax? c) Where do the students usually access or share information which contains hoax? d) What are the students’ perceptions toward the impact of hoaxes? The design of the study was a mixed method in which both questionnaire and interview were administered to the participants. Firstly, the written questionnaire was administered to elicit the respondents’ attitudes and other relevant questions. Further, semi-structured interview, which was conducted randomly, was employed to provide more elaborate data on the participants’ perception. The number of participants was 80 students of law department who are currently studying in their early semesters at one state university located in Serang, Banten. The result indicated that the participants disliked hoaxes. In average, 70 % of the whole respondents were identified to have negative attitudes, followed with the other supporting statements indicating their dislike toward hoaxes. However, despite the students’ negative attitudes toward hoaxes, they also admitted that they sometimes shared hoaxes. One reason found in the present study was to prevent possible harmful occurrences as indicated by 81, 25 % of respondents who admitted to do that, besides having fun. Finally, they also perceived that hoaxes were not as harmful as what the people have thought. This statement was supported by their objection toward the government’s action to penalize the perpetrator of hoaxes. Key words: Analysing, University students’ attitudes, Towards, Hoaxes